2020
DOI: 10.1037/dev0000994
|View full text |Cite
|
Sign up to set email alerts
|

Children’s attentional biases to emotions as sources of variability in their vulnerability to interparental conflict.

Abstract: Little is known about the role children's processing of emotions plays in altering children's vulnerability to interparental conflict. To address this gap, the present study examined whether the mediational cascade involving children's exposure to interparental conflict, their insecure responses to interparental conflict, and their psychological problems varied as a function of children's preexisting biases to attend to angry, fearful, sad, and happy expressions. Participants included 243 children (M age ϭ 4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 67 publications
2
14
0
Order By: Relevance
“…According to the sensitization model, emotional reactivity, behavioral dysregulation, and involvement may calibrate the emotional security system to become increasingly sensitive to emotions and threat cues. As a result, interparental difficulties and accompanying behavioral signs of insecurity may heighten children's tendencies to process emotions, especially for cues that signify threat (Davies, Thompson, et al, 2020). Thus, in the context of the current study, the sensitization model would be supported if behavioral signs of insecurity predicted a larger P3 response to adult emotions, especially angry emotions that more reliably signify threat.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…According to the sensitization model, emotional reactivity, behavioral dysregulation, and involvement may calibrate the emotional security system to become increasingly sensitive to emotions and threat cues. As a result, interparental difficulties and accompanying behavioral signs of insecurity may heighten children's tendencies to process emotions, especially for cues that signify threat (Davies, Thompson, et al, 2020). Thus, in the context of the current study, the sensitization model would be supported if behavioral signs of insecurity predicted a larger P3 response to adult emotions, especially angry emotions that more reliably signify threat.…”
Section: Introductionmentioning
confidence: 78%
“…In addition, although we sought to model our stimulus categories after previous ERP research on children exposed to adverse environments (Pollak et al, 1997), including additional categories of emotion in our stimulus set would have allowed us to address additional important questions. For example, including images depicting interpersonal fear would enable tests of additional questions about children's processing of threat-related stimuli, as well as more fully connecting this work with research using eye-tracking methods (Davies, Thompson, et al, 2020). In addition, based on a post hoc sensitivity analysis to determine the range of effect sizes that we were adequately powered to detect, we had insufficient power to detect small and medium effects.…”
Section: Primary Analysesmentioning
confidence: 99%
“…Supporting the role of affect‐biased attention as a plasticity factor, Davies et al (2020) found that children's attention to anger and fear moderated the prospective link between interparental conflict and their emotional insecurity in a for better and for worse fashion. Relative to children with diminished attention to angry and fearful faces, children exhibiting increased attention to angry and fearful faces evidenced both greater emotional insecurity in the context of heightened levels of interparental conflict and less emotional insecurity following exposure to minimal levels of interparental conflict.…”
Section: Moderating Role Of Affect‐biased Attentionmentioning
confidence: 99%
“…Because research examining the moderating role of children's affect‐biased attention has yet to specifically examine affect‐biased attention as a moderator of pathways between interparental conflict and children's distinct forms of involvement, these hypotheses are only speculative. Emphasizing the speculative nature of these hypotheses, previous studies examining the moderating role of affect‐biased attention have yielded mixed findings on whether greater or diminished attention to negative emotions amplifies children's reactivity to family risk (Briggs‐Gowan et al, 2015, 2016; Davies et al, 2020). Additionally, with the exception of a single study (Davies et al, 2020), research has not conducted systematic follow‐up tests to determine whether children's affect‐biased attention operates as a diathesis or a susceptibility factor in the context of family risk.…”
Section: Moderating Role Of Affect‐biased Attentionmentioning
confidence: 99%
“…For example, in their meta-analysis, Kitzman et al (2003) showed no statistically significant differences between IPV-exposed and physically abused children in terms of internalizing or externalizing behavior problems. Moreover, there is converging evidence from behavioral, psychophysiological, and neural studies that children exposed to IPV and adult partner conflict are hypersensitive to a variety of threat indices, including affective behavioral/attentional biases (Davies et al, 2020), autonomic reactivity (El-Sheikh, 2005), and enhanced activation in threat-processing regions in fMRI when viewing angry faces (McCrory et al, 2011). Moreover, neural indicators of sensitivity to threats may emerge as early as infancy (Graham et al, 2013).…”
mentioning
confidence: 99%